Microwave Assisted Extraction of Defatted Roselle (Hibiscus sabdariffa L.) Seed at Subcritical Conditions with Statistical Analysis - Yusoff, N. I.; Leo, C. P. (Hindawi Publishing Corporation, 2017)
Roselle seeds are the waste product of roselle processing, but they are now labeled as a polyphenol source with great herbal quality. In this work, polyphenols were extracted using ethanol-water (70% (v/v)) in a closed vessel under microwave irradiation. The main objective was to determine the optimal parameters statistically. The influence of extraction time (4–10 min), microwave power (100–300 W), and solvent/solid ratio (25–100 mL/g) was studied. The total phenolic and flavonoids content were determined using Folin-Ciocalteu and aluminum chloride methods, respectively.Without temperature control, the subcritical conditions could occur and the highest flavonoid content (14.4251mg QE/g) was achieved at 158∘C and 16.4 bar. Although the optimum MAE conditions (10 min, 300W, and 97.7178 mL/g) resulted in the highest yield (65.0367%) and phenolic content (18.2244mgGAE/g), lowflavonoids content (6.4524mg QE/g) was unexpectedly obtained due to degradation at 163∘C.